Ac4GlcNAcF3, an OGT-tolerated but OGA-resistant regulator for O-GlcNAcylation. Issue 6 (15th March 2019) - Wang, Haifeng; Guo, Jianshuang; Wang, Nan; Wang, Jiajia; Xue, Qingqing; Wang, Jiyan; Liu, Wenjie; Liu, Kaihui; Cao, Xuefeng; Zhao, Wei; Xi, Rimo; Niu, Youhong; et al.
Graphical abstract: Abstract: O -Linked N-acetylglucosamine ( O -GlcNAc) is an abundant posttranslational monosaccaride-modification found on Ser or Thr residues of intracellular proteins in most eukaryotes. The dynamic nature of O -GlcNAc has enabled researchers to modulate the stoichiometry of O -GlcNAc on proteins in order to investigate its function. Cell permeable small moleculars have proven invaluable tools to increase O -GlcNAc levels. Herein, using in vitro substrate screening, we identified GlcNAcF3 as an OGT-accepted but OGA-resistant sugar mimic. Cellular experiments with cell-permeable peracetylated-GlcNAcF3 (Ac4 GlcNAcF3 ) displayed that Ac4 GlcNAcF3 was a potent tool to increase O -GlcNAc levels in several cell lines. Further, NIH3T3 cells interfered with OGT (siOGT) showed significant decreasing of O -GlcNAc levels with Ac4 GlcNAcF3 treatment, indicating O -GlcNAcF3 was an OGT-dependent modification. In addition, cellular toxic assay confirmed O -GlcNAcF3 production has no significant effect on cell proliferation or viability. Thus, Ac4 GlcNAcF3 represents a safe and dual regulator for both OGT and OGA, which will benefit the study of O -GlcNAc.